Research progress of endoplasmic reticulum stress in peritoneal dialysis - Li Yan-ling; Zou Xun-liang (Linchuang shenzangbing zazhi)
Peritoneal dialysis is an effective renal replacement therapy for the treatment of end-stage renal disease. Prolonged peritoneal dialysis is prone to peritoneal inflammation， neoangiogenesis， and fibrosis， ultimately leading to interruption of peritoneal dialysis treatment. Recent studies have found that endoplasmic reticulum （ER） stress is closely related to peritoneal dialysis-associated complications. This article summarized the research progress of ER stress in peritoneal dialysis at home and abroad in recent years， mainly from the aspects of cell death， inflammatory signal transduction and epithelial-mesenchymal transition induced by ER stress through three classic signaling pathways， aiming to provide new ideas and directions for the prevention and treatment of peritoneal dialysis-related peritonitis and peritoneal fibrosis.